Relationships among fertility concerns, fear of cancer recurrence, social support, self-efficacy, and family resilience among Chinese adolescents and young adults with cancer: A structural equation modeling - YuQiao Xiao; Can Gu; Li Liu; XiaoRou Zeng (PLoS ONE, 2026)
Fertility concerns, fear of cancer recurrence, social support, and self-efficacy are key factors that influence family resilience in adolescents and young adults with cancer. However, their combined effects and underlying mechanisms remain unclear. This study constructed a structural equation model to examine these relationships and provide evidence for the development of targeted psychosocial interventions in clinical practice. A cross-sectional survey was conducted from April 2024 to March 2025 using convenience sampling of 259 adolescents and young adults with cancer at a tertiary-level specialized cancer hospital in Hunan Province. All the participants completed validated measures of fertility concerns, fear of cancer recurrence, social support, self-efficacy, and family resilience. A structural equation model was constructed using the AMOS software to test the hypothesized pathways. Correlation analysis revealed significant associations between all variables. The structural equation model demonstrated good fit. Path analysis revealed that fertility concerns and fear of recurrence exerted significant negative effects on family resilience, while social support and self-efficacy exerted significant positive effects. Further analysis revealed that social support and self-efficacy partially mediated the relationships between fertility concerns, fear of cancer recurrence, and family resilience. Family resilience among adolescent and young adult patients with cancer was significantly associated with fertility concerns, fear of cancer recurrence, social support, and self-efficacy. Social support and self-efficacy can mitigate and mediate the negative effects of fertility concerns and the fear of cancer recurrence on family resilience. Therefore, future clinical interventions should prioritize enhancing social support and self-efficacy among adolescents and young adults with cancer to alleviate fertility concerns and fear of cancer recurrence, thereby strengthening family resilience.